Α‐Synuclein evokes NLRP3 inflammasome‐mediated IL‐1β secretion from primary human microglia. Issue 6 (28th January 2021) - Pike, Adrianne F.; Varanita, Tatiana; Herrebout, Maaike A. C.; Plug, Bonnie C.; Kole, Jeroen; Musters, René J. P.; Teunissen, Charlotte E.; Hoozemans, Jeroen J. M.; Bubacco, Luigi; Veerhuis, Robert
Abstract: Synucleinopathies such as Parkinson's disease (PD) are hallmarked by α‐synuclein (α‐syn) pathology and neuroinflammation. This neuroinflammation involves activated microglia with increased secretion of interleukin‐1β (IL‐1β). The main driver of IL‐1β secretion from microglia is the NLRP3 inflammasome. A critical link between microglial NLRP3 inflammasome activation and the progression of both α‐syn pathology and dopaminergic neurodegeneration has been identified in various PD models in vivo. α‐Syn is known to activate the microglial NLRP3 inflammasome in murine models, but its relationship to this inflammasome in human microglia has not been established. In this study, IL‐1β secretion from primary mouse microglia induced by α‐syn fibrils was dependent on NLRP3 inflammasome assembly and caspase‐1 activity, as previously reported. We show that exposure of primary human microglia to α‐syn fibrils also resulted in significant IL‐1β secretion that was dependent on inflammasome assembly and involved the recruitment of caspase‐1 protein to inflammasome scaffolds as visualized with superresolution microscopy. While canonical IL‐1β secretion was clearly dependent on caspase‐1 enzymatic activity, this activity was less clearly involved for α‐syn‐induced IL‐1β secretion from human microglia. This work presents similarities between primary human and mouse microglia in the mechanisms of activation of the NLRP3 inflammasome by α‐syn, but also highlights evidence to suggest that there may be a difference in the requirement for caspase‐1 activity in IL‐1β output. The data represent a novel characterization of PD‐related NLRP3 inflammasome activation in primary human microglia and further implicate this mechanism in the pathology underlying PD. Main points: Primary human microglia undergo canonical inflammasome activation involving caspase‐1 α‐Syn fibrils activate the NLRP3 inflammasome in human microglia α‐Syn‐induced inflammasomes recruit caspase‐1; its activity may not be required for IL‐1β yield